Exploration of the Influence of Fatherlessness on Student Academics through the Perspective of Guidance Counseling Teachers - Miswala, Sakana Tiswi; Yusriyah, Yasmin Alifah (JUPE : Jurnal Pendidikan Mandala, 2025)
The phenomenon of fatherlessness, characterized by the physical or psychological absence of a father, has become a relevant issue in Indonesian education. This study aims to analyze the impact of fatherlessness on students' academic performance, the challenges faced by school counselors in addressing such students, and strategies implemented through Islamic Counseling Guidance (BKI). The research employs a qualitative approach using in-depth interviews and library research. The participants were experienced school counselors at SMK Negeri 04 Surakarta. The findings reveal that psychological fatherlessness significantly affects students' motivation and academic performance. School counselors face challenges such as lack of family support and resource limitations. BKI-based strategies, such as spiritual counseling and family relationship mediation, were found effective in improving the psychological state and academic outcomes of fatherless students.